MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Monitoring Photo-Fenton and Photo-Electro-Fenton process of contaminants emerging concern by a gas diffusion electrode using Ca10-xFex-yWy(PO4)6(OH)2 nanoparticles as heterogeneous catalyst - Fausto E.B. Júnior; Beatriz T. Marin; Leticia Mira; Carlos H.M. Fernandes; Guilherme V. Fortunato; Michell O. Almeida; Kathia M. Honório; Renata Colombo; Abner de Siervo; Marcos R.V. Lanza; Willyam R.P. Barros (Chemosphere, 2024)

Microstructure of Deposited AISI M4 High Speed Steel On AISI D2 Tool Steel Substrate Using L-DED Process - Giovanna F. Colombo; Moysés L. de Lima; Mário Boccalini; Alzira V. O. Corrêa; Marcelo T. Veiga (BHM Berg- und Hüttenmännische Monatshefte, 2024)

Control of particulate manganese (Mn) cycling in halocline Arctic Ocean waters by putative Mn‐oxidizing bacterial dynamics - Manuel Colombo; Julie LaRoche; Dhwani Desai; Jingxuan Li; Maria T. Maldonado (Limnology and Oceanography, 2023)
Particulate Mn, given its high adsorptive capacity and oxidation potential, has profound impacts on the cycling of various trace elements and organic matter in the ocean. Moreover, particulate Mn acts as a sink (via oxidation and adsorption) or as a source (via remineralization and photoreduction) term of bioactive dissolved Mn(II). In the Canadian Arctic Ocean, particulate Mn distributions in the water column revealed the presence of distinctively high particulate Mn concentrations and an overwhelming dominance of the non‐lithogenic component to the bulk particulate Mn pool. This phenomenon is of particular importance in halocline waters in the Canada Basin, the Canadian Arctic Archipelago and Baffin Bay, and near‐bottom samples in Baffin Bay. Enhanced microbially‐mediated Mn oxidation in the water column is suggested as the main mechanism driving the non‐lithogenic dominance. Indeed, the microbial community composition data associated with high non‐lithogenic particulate Mn (i.e., Mn oxides) display a high relative abundance of taxa (e.g., f.Pirellulaceae, o.Phycisphaerales, f.Cryomorphaceae, g. Moritella) that have been identified in Mn oxide enriched environments. Furthermore, numerous taxa identified in the Canada Basin halocline water, where non‐lithogenic particulate Mn peaked, are phylogenetically related to known (cultured) Mn‐oxidizing bacteria (MnOB; e.g., Rhodobacteraceae, Oceanospirillaceae, Rhizobiaceae, and other Alphaproteobacteria). Putative MnOB appears to proliferate in certain water masses having a unique set of environmental conditions: low light intensity—alleviating photoinhibition—and high dissolved Mn concentrations, the main drivers known to influence MnOB dynamic, and hence, Mn oxidation.

Identification of IPT9 in Brachiaria brizantha (syn. Urochloa brizantha) and expression analyses during ovule development in sexual and apomictic plants - Luciana G. Ferreira; Diva M. A. Dusi; André S. T. Irsigler; Ana C. M. M. Gomes; Lilian H. Florentino; Marta A. Mendes; Lucia Colombo; Vera T. C. Carneiro (Molecular Biology Reports, 2023)
Background In Brachiaria sexual reproduction, during ovule development, a nucellar cell differentiates into a megaspore mother cell (MMC) that, through meiosis and mitosis, gives rise to a reduced embryo sac. In aposporic apomictic Brachiaria , next to the MMC, other nucellar cells differentiate into aposporic initials that enter mitosis directly forming an unreduced embryo sac. The IPT (isopentenyltransferase) family comprises key genes in the cytokinin (CK) pathway which are expressed in Arabidopsis during ovule development. BbrizIPT9 , a B. brizantha ( syn. Urochloa brizantha ) IPT9 gene, highly similar to genes of other Poaceae plants, also shows similarity with Arabidopsis IPT9, AtIPT9 . In this work, we aimed to investigate association of BbrizIPT9 with ovule development in sexual and apomictic plants. Methods and results RT-qPCR showed higher BbrizIPT9 expression in the ovaries of sexual than in the apomictic B. brizantha . Results of in-situ hybridization showed strong signal of BbrizIPT9 in the MMC of both plants, at the onset of megasporogenesis. By analyzing AtIPT9 knockdown mutants, we verified enlarged nucellar cell, next to the MMC, in a percentage significantly higher than in the wild type, suggesting that knockout of AtIPT9 gene triggered the differentiation of extra MMC-like cells. Conclusions Our results indicate that AtIPT9 might be involved in the proper differentiation of a single MMC during ovule development. The expression of a BbrizIPT9 , localized in male and female sporocytes, and lower in apomicts than in sexuals, and effect of IPT9 knockout in Arabidopsis, suggest involvement of IPT9 in early ovule development.

Towards achieving circularity and sustainability in feeds for farmed blue foods - Stefanie M. Colombo; Koushik Roy; Jan Mraz; Alex H. L. Wan; Simon J. Davies; Sean M. Tibbetts; Margareth Øverland; David S. Francis; Melissa M. Rocker; Laura Gasco; Emma Spencer; Marc Metian; et al. (Reviews in Aquaculture, 2023)
The aims of this review are to describe the role of ‘blue‐food production’ (animals, plants and algae harvested from freshwater and marine environments) within a circular bioeconomy, discuss how such a framework can help the sustainability and resilience of aquaculture and to summarise key examples of novel nutrient sources that are emerging in the field of fed‐aquaculture species. Aquaculture now provides >50% of the global seafood supply, a share that is expected to increase to at least 60% within the next decade. Aquaculture is an important tool for reducing resource consumption in global protein production and increasing resilience to climate change and other global disruptions (i.e. pandemics, geo‐political instability). Importantly, blue foods also provide essential nutrition for a growing human population. Blue foods are helping to help the global goal of ‘zero hunger’ (United Nation's Sustainable Development Goal 2) while reducing the dependency on finite natural resources but further refinement and new solutions are needed to make the industry more ‘circular’ and sustainable, particularly with respect to sourcing raw materials for aquafeeds. This review describes the feed resources that are available or may be created within a circular bioeconomy framework, their role within the framework and in aquaculture and ultimately, how these resources contribute to de‐risking and establishing a resilient aquaculture production chain.

Exploratory analysis on Canadian consumer perceptions, habits, and opinions on salmon consumption and production in Canada - Angelisa T. Y. Osmond; Sylvain Charlebois; Stefanie M. Colombo (Aquaculture International, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nanopore Genome Sequencing and Variant Analysis of the Susceptible Candida auris Strain L1537/2020, Salvador, Brazil - Auke W. de Jong; Elaine C. Francisco; João Nóbrega de Almeida; Igor B. Brandão; Felicidade M. Pereira; Pedro H. Presta Dias; Magda M. de Miranda Costa; Regiane T. de Souza Jordão; Duong Vu; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2021)
Candida auris has been reported worldwide, but only in December 2020, the first strain from a COVID-19 patient in Brazil was isolated. Here, we describe the genome sequence of this susceptible C. auris strain and performed variant analysis of the genetic relatedness with strains from other geographic localities.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Projected declines in global DHA availability for human consumption as a result of global warming - Stefanie M. Colombo; Timothy F. M. Rodgers; Miriam L. Diamond; Richard P. Bazinet; Michael T. Arts (Ambio, 2020)
Docosahexaenoic acid (DHA) is an essential, omega-3, long-chain polyunsaturated fatty acid that is a key component of cell membranes and plays a vital role in vertebrate brain function. The capacity to synthesize DHA is limited in mammals, despite its critical role in neurological development and health. For humans, DHA is most commonly obtained by eating fish. Global warming is predicted to reduce the de novo synthesis of DHA by algae, at the base of aquatic food chains, and which is expected to reduce DHA transferred to fish. We estimated the global quantity of DHA (total and per capita) currently available from commercial (wild caught and aquaculture) and recreational fisheries. The potential decrease in the amount of DHA available from fish for human consumption was modeled using the predicted effect of established global warming scenarios on algal DHA production and ensuing transfer to fish. We conclude that an increase in water temperature could result, depending on the climate scenario and location, in a ~ 10 to 58% loss of globally available DHA by 2100, potentially limiting the availability of this critical nutrient to humans. Inland waters show the greatest potential for climate-warming-induced decreases in DHA available for human consumption. The projected decrease in DHA availability as a result of global warming would disproportionately affect vulnerable populations (e.g., fetuses, infants), especially in inland Africa (due to low reported per capita DHA availability). We estimated, in the worst-case scenario, that DHA availability could decline to levels where 96% of the global population may not have access to sufficient DHA.

Coupled Modeling of Sedimentary Basin and Geomechanics: A Modified Drucker–Prager Cap Model to Describe Rock Compaction in Tectonic Context - N. Guy; D. Colombo; J. Frey; T. Cornu; M. C. Cacas-Stentz (Rock Mechanics and Rock Engineering, 2019)

Synthesis and evaluation of the antileishmanial activity of silver compounds containing imidazolidine-2-thione - Patrícia Ferreira Espuri; Larissa Luiza dos Reis; Eduardo de Figueiredo Peloso; Vanessa Silva Gontijo; Fábio Antônio Colombo; Juliana Barbosa Nunes; Carine Ervolino de Oliveira; Eduardo T. De Almeida; Débora E. S. Silva; Jessica Bortoletto; Daniel Fonseca Segura; Adelino V. G. Netto; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

The growth and contamination mechanism of the Cana Brava layered mafic-ultramafic complex: new field and geochemical evidences - Tommaso Giovanardi; Vicente A. V. Girardi; Ciro T. Correia; Silvano Sinigoi; Colombo C. G. Tassinari; Maurizio Mazzucchelli (Mineralogy and Petrology, 2017)

A follow-up study examining airborne Ambrosia pollen in the Milan area in 2014 in relation to the accidental introduction of the ragweed leaf beetle Ophraella communa - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; Ł. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Effect of age and disturbance on decadal changes in carbon stocks in managed forest landscapes in central Canada - Michael T. Ter-Mikaelian; Stephen J. Colombo; Jiaxin Chen (Mitigation and Adaptation Strategies for Global Change, 2014)

Trends in Surface Water Chemistry in Acidified Areas in Europe and North America from 1990 to 2008 - Øyvind A. Garmo; Brit Lisa Skjelkvåle; Heleen A. de Wit; Luca Colombo; Chris Curtis; Jens Fölster; Andreas Hoffmann; Jakub Hruška; Tore Høgåsen; Dean S. Jeffries; W. Bill Keller; Pavel Krám; et al. (Water, Air, & Soil Pollution, 2014)

The ecological and genetic basis of convergent thick‐lipped phenotypes in cichlid fishes - Marco Colombo; Eveline T. Diepeveen; Moritz Muschick; M. EMILIA Santos; Adrian Indermaur; Nicolas Boileau; Marta Barluenga; Walter Salzburger (Molecular Ecology, 2013)
The evolution of convergent phenotypes is one of the most interesting outcomes of replicate adaptive radiations. Remarkable cases of convergence involve the thick‐lipped phenotype found across cichlid species flocks in the E ast A frican G reat L akes. Unlike most other convergent forms in cichlids, which are restricted to E ast A frica, the thick‐lipped phenotype also occurs elsewhere, for example in the C entral A merican M idas C ichlid assemblage. Here, we use an ecological genomic approach to study the function, the evolution and the genetic basis of this phenotype in two independent cichlid adaptive radiations on two continents. We applied phylogenetic, demographic, geometric morphometric and stomach content analyses to an A frican ( L obochilotes labiatus ) and a C entral A merican ( A mphilophus labiatus ) thick‐lipped species. We found that similar morphological adaptations occur in both thick‐lipped species and that the ‘fleshy’ lips are associated with hard‐shelled prey in the form of molluscs and invertebrates. We then used comparative I llumina RNA sequencing of thick vs. normal lip tissue in E ast A frican cichlids and identified a set of 141 candidate genes that appear to be involved in the morphogenesis of this trait. A more detailed analysis of six of these genes led to three strong candidates: A ctb , C ldn7 and C opb . The function of these genes can be linked to the loose connective tissue constituting the fleshy lips. Similar trends in gene expression between A frican and C entral A merican thick‐lipped species appear to indicate that an overlapping set of genes was independently recruited to build this particular phenotype in both lineages.

Acoustic survey of a jellyfish-dominated ecosystem (Mljet Island, Croatia) - G. Alvarez Colombo; A. Benović; A. Malej; D. Lučić; T. Makovec; V. Onofri; M. Acha; A. Madirolas; H. Mianzan (Hydrobiologia, 2009)

Validation of precipitation events in a regional climate model simulation using methods from complex systems theory - V. Pelino; A. Matera; T. Colombo; F. Giorgi (Theoretical and Applied Climatology, 2006)

Robot-aided neurorehabilitation of the upper extremities - R. Riener; T. Nef; G. Colombo (Medical & Biological Engineering & Computing, 2005)

Soil microbial diversity and community structure across a climatic gradient in western Canada - William J. Staddon; Jack T. Trevors; Luc C. Duchesne; Carol a. Colombo (Biodiversity and Conservation, 1998)

Free circulating magnesium and loop diuretics in humans - T. Gozzi; S. Dürler; A. C. Truttman; J. P. Colombo; M. G. Bianchetti (European Journal of Clinical Pharmacology, 1997)